Rebel returnees and their responses to government integration policies and programs in Western Mindanao - Ko, Bernabela De Leon 1926- (1980)
The relationship between the rebel-returnees' personal characteristics, socio-economic level, socio-cultural status, political consciousness, value orientations and environmental experiences on one hand and their attitude towards the government and its integration policies and programs on the other were taken into consideration in this study. The findings showed that the attitudes toward government integration policies and programs are not significantly different despite differences in personal characteristics, socio-economic status, socio-cultural status, political consciousness, value orientation and environmental experiences. The similarities in attitude towards government integration policies and programs imply that Muslims, on the whole, are receptive to changes directed towards their betterment
Mimeographed.
Thesis (D.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Tausugs -- Politics and government; Yakans -- Politics and government; Western Mindano -- Politics and government